Influence of Community Knowledge and Attitude with Dengue Fever Prevention Behavior (DHF) in the Padang Cermin Health Center Working Area - Chanita Sari Manulang; Samino; Khoidar Amirus; Fitri Eka Sari (Postgraduate, University of Mataram, 2023)
Dengue Hemorrhagic Fever (DHF) is a type of acute febrile illness caused by one of the four serotypes of the virus again with the genus Flavivirus known as the dengue virus which is characterized by bleeding fever 2 to 7 days without clear cause weakness, lethargy, anxiety, heartburn accompanied by signs of bleeding in the skin in the form of bleeding spots. The purpose of this study was to determine the effect of community knowledge and attitudes on dengue prevention behavior in the working area of the padang cermin health center.This type of research uses quantitative research with a cross sectional approach.The study population was the head of the family in the health center working area with a sample of 145 families selected by purposive sampling using a questionnaire. The results showed that there was an influence of knowledge obtained a value of knowledge (r=0.604; P Value 0.001 <0.05) attitude (r=0.732; P value 0.001 <0.05) with dengue prevention behavior. The results of hypothesis testing are that there is a positive relationship between knowledge and attitude with dengue prevention behavior. Suggestions from researchers, namely, the need to increase public knowledge by the Puskesmas through socialization and education activities to prevent dengue hemorrhagic fever routinely once a month, promotion to the community can be done with social media such as WhatsApp, Instagram and Facebook so that information can reach the community more quickly.